Perlindungan Hukum Pada Perjanjian Kerja Waktu Tertentu (PKWT) Ditinjau dari Jaminan Hak-Hak Pekerja (Undang-Undang NRI Nomor 13 Tahun 2003) - Maulandari, Fenanda Dwi; Musfianawati, Musfianawati; Setiawan, Sidi Alkahfi; A. Razaq, Moh. Khalilullah (WELFARE STATE Jurnal Hukum, 2025)
Legal protection is a right that every citizen should be able to enjoy equally and fairly from their government. However, in reality there are still many people who do not receive proper legal attention or protection. Law NRI Number 13 of 2003 concerning Employment, here in after referred to as UUK in Indonesia, is a law that is used to regulate all matters related to or related to workers’ labor and tenure. This research examines legal protection in fixed-team work agreements (PKWT) in terms of workers’ rights guarantess according to Law. The research method used uses an approach through statutory regulations. The research result show that the Specific Time Work Agreement (PKWT) provides legal protection to workers, although there are several weaknesses that need to be corrected. It is important to continue to improve and strengthen legal protection for workers who are bound by a (PKWT) in accordance with the provisions of the Law.